2015
DOI: 10.1038/ncomms8972
|View full text |Cite
|
Sign up to set email alerts
|

Slow-growing cells within isogenic populations have increased RNA polymerase error rates and DNA damage

Abstract: Isogenic cells show a large degree of variability in growth rate, even when cultured in the same environment. Such cell-to-cell variability in growth can alter sensitivity to antibiotics, chemotherapy and environmental stress. To characterize transcriptional differences associated with this variability, we have developed a method—FitFlow—that enables the sorting of subpopulations by growth rate. The slow-growing subpopulation shows a transcriptional stress response, but, more surprisingly, these cells have red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 53 publications
5
53
0
Order By: Relevance
“…For simulation details, see Supporting Information Section S3. proliferation rate of yeast is heritable, and that slow-growing cells have higher oxidative stress whose proliferation rate may be rescued with an anti-oxidant, suggesting a link to mitochondrial functionality [56]. Further studies are required to determine whether this is true for a larger class of systems, including mammalian cells.…”
Section: Box 1 Allometric Scaling Hypothesis Of Cellular Power Demandsmentioning
confidence: 99%
See 1 more Smart Citation
“…For simulation details, see Supporting Information Section S3. proliferation rate of yeast is heritable, and that slow-growing cells have higher oxidative stress whose proliferation rate may be rescued with an anti-oxidant, suggesting a link to mitochondrial functionality [56]. Further studies are required to determine whether this is true for a larger class of systems, including mammalian cells.…”
Section: Box 1 Allometric Scaling Hypothesis Of Cellular Power Demandsmentioning
confidence: 99%
“…The biological mechanism for the heritability of mitochondrial functionality was unclear from that study, although one may speculate that the inherited concentration of mitochondrial fusion proteins may be a feasible explanation for this. Indeed, recent evidence suggests that the proliferation rate of yeast is heritable, and that slow-growing cells have higher oxidative stress whose proliferation rate may be rescued with an anti-oxidant, suggesting a link to mitochondrial functionality [56]. Further studies are required to determine whether this is true for a larger class of systems, including mammalian cells.…”
Section: A Parabolic Function Of Mitochondrial Functionality Against mentioning
confidence: 99%
“…For example, some isogenic cells within cultures of Saccharomyces cerevisiae can survive extreme heat stress whereas most cells in the culture cannot (10). Stress-tolerant individuals may be in an altered state, since they often display transiently reduced growth and markers of the stress response (1,(10)(11)(12). But whether this state mimics that of stress-treated cells that have fully mounted a stress response or instead emerges from partial, stochastic events is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work showed that such fluctuations can impact the mean population growth 49 , implying that these mechanistic parameters may be subject to evolutionary pressure. Cellular physiology could seize this degree of freedom and use it to shape noise to its benefit, for instance, as an evolutionary bet-hedging strategy [50][51][52] . The model could be put to use in in numero evolutionary experiments to test the specific benefits of noise architectures in different environments and retrace possible evolutionary paths.…”
Section: Discussionmentioning
confidence: 99%